2022
DOI: 10.3991/ijet.v17i11.30265
|View full text |Cite
|
Sign up to set email alerts
|

A Ubiquitous Learning Model for Education and Training Processes Supported by TV Everywhere Platforms

Abstract: Advances in technology and digital convergence, for example Netflix, enable users to view TV and video without time or place restrictions. These advances can be applied in education and training processes to enable ubiquitous learning (u-learning). However, a literature review (of the years 2002 to 2018) on u-learning models yielded scarce information about its implementation, specifically demonstrating a lack of application alternatives that could provide access to TV regardless of place and device. To contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…These characteristics expedited access to information, enabled discussions among trainees and between them and the trainer, and allowed trainees to document their ideas about the training topic. Additionally, the results of the current study agree with the results of several studies (e.g., Giordano & Marongiu, 2021;Ismail, 2016;Liu et al, 2020;Moreno-López et al, 2022;Mustafa, 2019;Ramzy, 2019;Shalaby & Murad, 2017;Soy-Muner, 2020;Yang et al, 2021) that indicate the effectiveness of EDPs in developing cognitive and skill aspects. Mustafa's (2019) study confirmed the effectiveness of EDPs in developing children's e-magazine production skills.…”
Section: Discussionsupporting
confidence: 91%
“…These characteristics expedited access to information, enabled discussions among trainees and between them and the trainer, and allowed trainees to document their ideas about the training topic. Additionally, the results of the current study agree with the results of several studies (e.g., Giordano & Marongiu, 2021;Ismail, 2016;Liu et al, 2020;Moreno-López et al, 2022;Mustafa, 2019;Ramzy, 2019;Shalaby & Murad, 2017;Soy-Muner, 2020;Yang et al, 2021) that indicate the effectiveness of EDPs in developing cognitive and skill aspects. Mustafa's (2019) study confirmed the effectiveness of EDPs in developing children's e-magazine production skills.…”
Section: Discussionsupporting
confidence: 91%
“…The second category includes a meta-analysis of doi: U-learning, such as a meta-analysis of the effects of augmented reality technologies in interactive learning environments [12], and a U-learning model for education and training processes supported by television platforms. A literature review between 2002 and 2018 on U-learning models yielded little information about its implementation; in particular, this demonstrated a lack of alternatives that could provide access to television regardless of place and device [13].…”
Section: Introductionmentioning
confidence: 99%
“…They may study on the go thanks to flexible learning methods like the internet that do not require cumbersome ground wire attachments or a set location. In addition to solving numerous educational issues for a large number of future generations, the advancement of educational technology using mobile and other wire-free devices has demonstrated the value of using widespread education among academics, professors, and students (Moreno López et al, 2022). This has demonstrated the effectiveness and adaptability of learning through the use of devices that have been developed and diversified in methods.…”
Section: Introductionmentioning
confidence: 99%